Development of core-shell magnetic molecularly imprinted polymer-based electrochemical sensor for sensitive and selective detection of ezetimibe - Ayemeh Bagheri Hashkavayi; Abdolhossein Alizadeh; Razieh Azimi; Moazameh Peyrovi; Jahan Bakhsh Raoof; Honggu Chun (Heliyon, 2023)
A sensitive electrochemical molecularly imprinted polymer (MIP) sensor was fabricated for detection of ezetimibe (Eze) as an effective cholesterol absorption inhibitor on the surface of a screen-printed carbon electrode based on a magnetic nanoparticle decorated with MIP (Fe3O4@MIP). Placing the magnetic nanoparticle inside the MIP increases the biocompatibility, surface-to-volume ratio, and sensitivity of the sensor. Methacrylic acid (MAA) was used as a monomer, ethylene glycol dimethacrylate (EGDMA) as a cross-linker, and Eze as a template. The fabricated Fe3O4@MIP was characterized using Fourier-transform infrared spectroscopy (FTIR), Transmission electron microscopy (TEM), and scanning electron microscopy (SEM). Detection of Eze was achieved by differential pulse voltammetry. Using this sensor, Eze can be sensitively detected in the range of 1.0 nM–10 μM and detection limit of 0.7 nM. In addition, we have shown that the proposed sensor successfully detects different concentrations of Eze in human serum samples and thus proves its practical application.